Nationalism and Ethnosymbolism: History, Culture and Ethnicity in the Formation of Nations (Edinburgh, 2007)
Ethnosymbolism offers a distinct and innovative approach to the study of nations and nationalism. It focuses on the role of ethnic myths, historical memories, symbols and traditions in the creation and maintenance of the collective identity of modern nations. This book explores the different aspects of the ethnosymbolic approach to the study of ethnicity, nationality and nationalism.Nationalism and Ethnosymbolism first introduces the main theoretical considerations that have arisen in nationalism studies in the past two decades. It then presents a collection of case studies covering music and poetry, ethnosymbolism in antiquity, and a wide variety of nations and regions. Areas discussed include Eastern Europe and Russia, the Middle East, the Far East and India, Africa, and the Americas.Overall the book offers a defence of the methodology of ethnosymbolism and a demonstration of its explanatory power.Key Features:* Includes contributions from some of the most eminent scholars in the field of nationalism studies including Anthony D. Smith, the doyen of ethnosymbolism* Offers a distinctive approach to the analysis of ethnicity and nationalism in the modern world* Ethnosymbolism is now a key element of the nationalism studies discourse* The ethnosymbolic approach can be applied to the analysis of a variety of historical and contemporary social, cultural and political situations